Predictive value of oncogenic driver subtype, programmed death‐1 ligand (PD‐L1) score, and smoking status on the efficacy of PD‐1/PD‐L1 inhibitors in patients with oncogene‐driven non–small cell lung cancer. Issue 7 (11th December 2018) - Ng, Terry L.; Liu, Yiwei; Dimou, Anastasios; Patil, Tejas; Aisner, Dara L.; Dong, Zhengwei; Jiang, Tao; Su, Chunxia; Wu, Chunyan; Ren, Shengxiang; Zhou, Caicun; Camidge, D. Ross
Abstract : Background: This multicenter, retrospective study explored the value of oncogene driver subtype, programmed death‐1 ligand (PD‐L1) status, and smoking status for predicting which patients with oncogene‐driven non–small cell lung cancer (NSCLC) would benefit from treatment with programmed death‐1 (PD‐1)/PD‐L1 inhibitors. Methods: The clinical features, PD‐L1 tumor proportion scores, and PD‐1/PD‐L1 inhibitor (PDi) outcomes (objective response rate and progression‐free survival) of patients who had advanced NSCLC with Kirsten rat sarcoma 2 viral oncogene homolog ( KRAS ) mutations or common, actionable oncogenic drivers were captured. Results: In total, 189 oncogene‐positive patients were analyzed. Of these, 104 received a PDi, and 108 had undergone prior PD‐L1 testing. The frequency of PD‐L1 positivity (≥1%) was higher in patients who had KRAS mutations ( P = .031), smokers ( P = .006), and non‐Asian patients ( P = .002). Multivariable analysis indicated that smoking status ( P < .001) was the only factor associated significantly with KRAS mutation. The objective response rate to PDi treatment was 16.9% (11 of 65 patients) among smokers (17.3% in the KRAS ‐mutant and 15.4% in the non‐ KRAS –mutant smoker subgroups), which was significantly higher than the 0% rate (0 of 26 patients; P = .019) among never‐smokers. In subgroup analyses, progression‐free survival was influenced by KRAS mutation status (median, 4.57 vs 1.63 months; P = .004), smoking status (4.07 vs 1.73 months; P = .004), PD‐L1 positivity (3.8 vs 1.2 months; P = .040), and non‐Asian race (3.0 vs 1.97 months; P = .046). In multivariable analysis, only smoking status ( P = .008) remained a significant predictor when a PD‐L1 level ≥1% was used. However, both smoking status ( P = .001) and PD‐L1 status ( P = .028) were independent predictors when a PD‐L1 level ≥50% was used. Conclusions: Among associated clinical features among patients who have NSCLC with oncogenic drivers, smoking status potentially was the most important, easily available predictor of single PDi efficacy. Abstract : Potential markers for predicting the efficacy of programmed death‐1/programmed death‐1 ligand (PD‐1/PD‐L1) inhibitors in patients who have non–small cell lung cancer with oncogenic driver mutations remain unclear. Results from this multicenter analysis in a cohort of 189 patients with non–small cell lung cancer indicate that smoking history may be the most important, easily available predictor of benefit from anti–PD‐1/PD‐L1 monoclonal antibody monotherapy, and positive PD‐L1 status appears to influence outcomes only at high levels.